Imbalanced Expression of Tau and Tubulin Induces Neuronal Dysfunction in C. elegans Models of Tauopathy - Miyasaka, Tomohiro; Shinzaki, Yuki; Yoshimura, Satomi; Yoshina, Sawako; Kage-Nakadai, Eriko; Mitani, Shohei; Ihara, Yasuo (Frontiers in Neuroscience, 2018)
Tauopathy is a type of dementia defined by the accumulation of filamentous tau inclusions in neural cells. Most types of dementia in the elderly, including Alzheimer’s disease, are tauopathies. Although it is believed that tau protein abnormalities and/or the loss of its functions results in neurodegeneration and dementia, the mechanism of tauopathy remains obscure. Loss of microtubules and/or tubulin is a known consequence of tau accumulating in neurons in Alzheimer’s disease. In other words, there is an excess level of tau relative to tubulin in tauopathy neurons. To test whether this imbalance of tau and tubulin expression results in the neurotoxicity of tau, we developed several transgenic C. elegans lines that express human tau at various levels in pan-neurons. These worms showed behavioral abnormalities in a tau expression-dependent manner. The knockdown of a tubulin-specific chaperon, or a subset of tubulin, led to enhanced tau toxicity even in low-expressing tau-transgenic worms that showed no abnormal behaviors. In addition, the suppression of tau expression in tubulin knockdown worms rescued neuronal dysfunction. Thus, not only the overexpression of tau but also a reduction in tubulin can trigger the neurotoxicity of tau. Tau expressed in worms was also highly phosphorylated and largely bound to tubulin dimers rather than microtubules. Relative amount of tubulin-unbound tau was increased in high-expressing tau-transgenic worms showing tau toxicity. We further demonstrated that tau aggregation was inhibited by co-incubation of purified tubulin in vitro, meaning sufficient amounts of tubulin can protect against the formation of tau inclusions. These results suggest that the expression ratio of tau to tubulin may be a determinant of the tauopathy cascade.